2007
DOI: 10.1007/s10350-007-9081-7
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Wound Infusion of Local Anesthetic for the Control of Pain After Elective Abdominal Colorectal Surgery

Abstract: Management of pain after major abdominal colorectal surgery is best achieved through adopting a multimodal approach to analgesia. Delivery of ropivacaine to midline laparotomy wounds via a Painbuster Soaker device is safe, but we have not demonstrated any significant clinical advantage over current best practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 22 publications
2
41
1
7
Order By: Relevance
“…After screening, 5 randomised controlled trials were identified [22][23][24][25][26] . The five trials included 542 laparotomy wounds, of which 259 were randomised to infusion of local anaesthetic agents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening, 5 randomised controlled trials were identified [22][23][24][25][26] . The five trials included 542 laparotomy wounds, of which 259 were randomised to infusion of local anaesthetic agents.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the five trials reported separate data for opioid consumption with or without local anaesthetic wound infusion on post-operative day 1 [22,23,25,26] ( Figure 1B). Local anaesthetic wound infusion was associated with a significant decrease in opioid consumption on postoperative day 1 (weighted mean difference: -8.34; 95% CI: -16.38 to -0.31; P = 0.04).…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Šis metodas tinkamiausias didelės apimties, traumuojančioms operacijoms, kurios reikalauja didelio chirurginio pjū-vio bei atlikimo laiko [21]. Taip galima palaikyti nuolatinę efektyvią anestetiko koncentraciją žaizdoje ir esant poreikiui ją padidinti ar sumažinti [29]. Kaip pavyzdį pateiksime E. Forastiere ir bendraautorių atliktą tyrimą naudojant nuolatinę operacinės žaizdos infuziją po atvirų inkstų pašalinimo operacijų.…”
Section: Skausmo Malšinimas Metodaiunclassified
“…Kol kas svari žaizdų infiltracijos anestetikais nauda stebima po kirkšninės iš-varžos operacijų [4, 15,24]. Po kitų abdominalinių operacijų šio nuskausminimo naudai įrodyti ir rekomendacijoms sukurti reikia atlikti daugiau tyrimų, kuriuose būtų įvertinami ir finansiniai aspektai [7,16,29] . Akušerija/ginekologija.…”
Section: Skausmo Malšinimas Metodaiunclassified